Development of a family-based treatment for co-occurring intimate partner violence and child maltreatment: the MST-IPV model - Cynthia Cupit Swenson; Cindy M. Schaeffer (BJPsych Bulletin)
Intimate partner violence (IPV) is a significant global problem that affects the health of children, parents/caregivers and extended family. The effects can be lifelong and span generations. Treatments for IPV are focused largely on individual work with men as the primary aggressor. Even when the situation includes child maltreatment, generally all family members are referred to a host of providers for varied treatments. Traditionally, couples and family work does not occur. In this article, we detail the development and practice of a comprehensive treatment model for complex cases of co-occurring IPV and child maltreatment that is inclusive of the family and couple. Of particular note, the development of this model, Multisystemic Therapy for Intimate Partner Violence (MST-IPV), involved input from the IPV stakeholder community.